Targeted manipulation of pain neural networks: The potential of focused ultrasound for treatment of chronic pain. (August 2020) - Todd, Nick; McDannold, Nathan; Borsook, David
Highlights: Focused ultrasound treatments in the brain have recently entered the clinic. Applications to the treatment of chronic pain are currently understudied. The technology can target aberrantly functioning nodes of the pain network. A review of the pre-clinical and clinical literature suggests an opportunity. Abstract: Focused ultrasound (FUS) is a promising technology for facilitating treatment of brain diseases including chronic pain. Focused ultrasound is a unique modality for delivering therapeutic levels of energy into the body, including the central nervous system (CNS). It is non-invasive and can target spatially localized effects through the intact skull to cortical or subcortical regions of the brain. FUS can achieve three different mechanisms of action in the brain that are relevant for chronic pain treatment: (1) localized thermal ablation of neural tissue; (2) localized and transient disruption of the blood-brain barrier for targeted drug delivery to CNS structures; and (3) inhibition or stimulation of neuronal activity in targeted regions. This review provides an in-depth look at the technology of FUS with emphasis placed on applications to CNS-based treatments of chronic pain. While still in the early stages of clinical translation and with some technical challenges remaining, we suggest that FUS has great potential as a novel approach for manipulating CNS networks involved in pain treatment.